2017
DOI: 10.1186/s12917-017-1210-5
|View full text |Cite
|
Sign up to set email alerts
|

Quadruplex PCR assay for identification of Corynebacterium pseudotuberculosis differentiating biovar Ovis and Equi

Abstract: Background Corynebacterium pseudotuberculosis is classified into two biovars, nitrate-negative biovar Ovis which is the etiologic agent of caseous lymphadenitis in small ruminants and nitrate-positive biovar Equi, which causes abscesses and ulcerative lymphangitis in equines. The aim of this study was to develop a quadruplex PCR assay that would allow simultaneous detection and biovar-typing of C. pseudotuberculosis.MethodsIn the present study, genomes of C. pseudotuberculosis strains were used to identify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Sterile panniculitis, diagnosed with histological investigation and negative bacterial culture, was diagnosed in three donkeys in our study but only reported once previously . Corynebacterium pseudotuberculosis, a pathogen well investigated in horses, was isolated from three cases in our study, one of which was reported in a review article . Another rarely reported pathogen in donkeys, Sporothrix schenckii, was seen in one of our cases .…”
Section: Discussionsupporting
confidence: 51%
“…Sterile panniculitis, diagnosed with histological investigation and negative bacterial culture, was diagnosed in three donkeys in our study but only reported once previously . Corynebacterium pseudotuberculosis, a pathogen well investigated in horses, was isolated from three cases in our study, one of which was reported in a review article . Another rarely reported pathogen in donkeys, Sporothrix schenckii, was seen in one of our cases .…”
Section: Discussionsupporting
confidence: 51%
“…C. pseudotuberculosis can be distinguished into two biovars based on its ability to reduce nitrate. Nitrate-negative strains are classified as biovar Ovis and nitrate-positive ones as biovar Equi [ 20 , 21 , 22 ]. In sheep and goats, CLA is predominantly caused by biovar Ovis, whereas the nitrate-positive biovar is the causative agent of abscesses and ulcerative lymphangitis in horses and oedematous skin disease (OSD) in buffaloes [ 2 , 4 , 7 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quadruplex PCR reactions were performed with a final volume of 50 µL, containing 20 ng of genomic DNA, 0.25 mM dNTPs, 0.1 unit of Taq DNA polymerase (Life Technologies, Carlsbad, CA, USA), 2 mM MgCl 2, enzyme buffer (Life Technologies, Carlsbad, CA, USA), 0.5 µM of each primer oligonucleotide, and water to a final volume of 50 µL. The primers used in this study anneal to the 16s rRNA, rpoB, narG, and pld gene sequences of Corynebacterium pseudotuberculosis, in accordance with Almeida et al [24]. The amplified products were resolved through electrophoresis on 1.0% (w/v) agarose gels and stained using ethidium bromide.…”
Section: Case Descriptionmentioning
confidence: 81%